Factors associated with dengue shock syndrome: a systematic review and meta-analysis. - Nguyen Tien Huy; Tran Van Giang; Dinh Ha Duy Thuy; Mihoko Kikuchi; Tran Tinh Hien; Javier Zamora; Kenji Hirayama (Public Library of Science (PLoS), 2013)
The pathogenesis of dengue shock syndrome (DSS, grade 3 and 4) is not yet completely understood. Several factors are reportedly associated with DSS, a more severe form of dengue infection that reportedly causes 50 times higher mortality compared to that of dengue patients without DSS. However, the results from these reports remain inconclusive. To better understand the epidemiology, clinical manifestation, and pathogenesis of DSS for development of new therapy, we systematically reviewed and performed a meta-analysis of relevant studies that reported factors in both DSS and dengue hemorrhagic fever (DHF, grade 1 and 2) patients.PubMed, EMBASE, Scopus, Google Scholar, Dengue Bulletin, Cochrane Library, Virtual Health Library, and a manual search of reference lists of articles published before September 2010 were used to retrieve relevant studies. A meta-analysis using fixed- or random-effects models was used to calculate pooled odds ratios (OR) or event rate with corresponding 95% confidence intervals. Assessment of heterogeneity and publication bias, meta-regression analysis, subgroup analysis, sensitivity analysis, and analysis of factor-specific relationships were further performed. There were 198 studies constituting 203 data sets that met our eligibility criteria. Our meta-regression analysis showed a sustained reduction of DSS/dengue hemorrhagic fever (DHF) ratio over a period of 40 years in Southeast Asia, especially in Thailand. The meta-analysis revealed that age, female sex, neurological signs, nausea/vomiting, abdominal pain, gastrointestinal bleeding, hemoconcentration, ascites, pleural effusion, hypoalbuminemia, hypoproteinemia, hepatomegaly, levels of alanine transaminase and aspartate transaminase, thrombocytopenia, prothrombin time, activated partial thromboplastin time, fibrinogen level, primary/secondary infection, and dengue virus serotype-2 were significantly associated with DSS when pooling all original relevant studies.The results improve our knowledge of the pathogenesis of DSS by identifying the association between the epidemiology, clinical signs, and biomarkers involved in DSS.